2015
DOI: 10.1093/annonc/mdu584
|View full text |Cite
|
Sign up to set email alerts
|

A randomized phase III trial of stereotactic radiosurgery (SRS) versus observation for patients with asymptomatic cerebral oligo-metastases in non-small-cell lung cancer

Abstract: NCT01301560.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
51
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(56 citation statements)
references
References 26 publications
3
51
0
2
Order By: Relevance
“…SRS followed by chemotherapy in NSCLC with brain metastases resulted in a median OS of 14.6 months, similar to the 15.3 months reported for chemotherapy alone in a study by Lim et al, with the SRS arm reporting lower central nervous system (CNS) symptomatic progression rates than the chemotherapy alone arm (18.4% vs 26.5%) [6]. Rades et al showed that SRS had a local control rate of P75% in brain metastases [51].…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…SRS followed by chemotherapy in NSCLC with brain metastases resulted in a median OS of 14.6 months, similar to the 15.3 months reported for chemotherapy alone in a study by Lim et al, with the SRS arm reporting lower central nervous system (CNS) symptomatic progression rates than the chemotherapy alone arm (18.4% vs 26.5%) [6]. Rades et al showed that SRS had a local control rate of P75% in brain metastases [51].…”
Section: Discussionsupporting
confidence: 79%
“…Median OS of more than 12 months has been reported in a series of patients treated with this technique [6,7]. Molecularly targeted therapies including epidermal growth factor receptor (EGFR) inhibitors and anaplastic lymphoma kinase (ALK) inhibitors are being evaluated for the treatment of brain metastases in molecularly selected NSCLC patients, with initial reports of a median survival time around 12 months [5].…”
Section: Introduction and Rationalementioning
confidence: 99%
“…Treatment with radiosurgery was well tolerated and there was no difference in neurocognitive function between the two study groups. 16 (A) Even when the tumor is located in critical areas, radiosurgery is feasible. Luther et al observed that motor function improves by 31% or remains stable in 50% of patients with brain metastases located in the motor cortex treated with radiosurgery.…”
Section: What Is the Toxicity Of Radiosurgery Formentioning
confidence: 99%
“…Lim et al randomized 105 patients with NSCLC and less than 4 BMs to receive SRS followed by a platinum-based doublet or a platinum-based doublet alone (68). Although the study included a smaller sample size than initially anticipated due to early termination, SRS followed by chemotherapy did not improve OS compared with upfront chemotherapy (median OS was 14.6 and 15.3 months in the SRS arm and upfront chemotherapy arm, respectively).…”
Section: Concurrent Chemotherapy and Radiotherapy For Bms From Nsclcmentioning
confidence: 99%